Engineered Biopolymeric Scaffolds for Chronic Wound Healing - Dickinson, Laura E.; Gerecht, Sharon (Frontiers in Physiology, 2016)
Skin regeneration requires the coordinated integration of concomitant biological and molecular events in the extracellular wound environment during overlapping phases of inflammation, proliferation, and matrix remodeling. This process is highly efficient during normal wound healing. However, chronic wounds fail to progress through the ordered and reparative wound healing process and are unable to heal, requiring long-term treatment at high costs. There are many advanced skin substitutes, which mostly comprise bioactive dressings containing mammalian derived matrix components and/or human cells, in clinical use. However, it is presently hypothesized that no treatment significantly outperforms the others. To address this unmet challenge, recent research has focused on developing innovative acellular biopolymeric scaffolds as more efficacious wound healing therapies. These biomaterial-based skin substitutes are precisely engineered and fine-tuned to recapitulate aspects of the wound healing milieu and target specific events in the wound healing cascade to facilitate complete skin repair with restored function and tissue integrity. This mini-review will provide a brief overview of chronic wound healing and current skin substitute treatment strategies while focusing on recent engineering approaches that regenerate skin using synthetic, biopolymeric scaffolds. We discuss key polymeric scaffold design criteria, including degradation, biocompatibility, and microstructure, and how they translate to inductive microenvironments that stimulate cell infiltration and vascularization to enhance chronic wound healing. As healthcare moves towards precision medicine-based strategies, the potential and therapeutic implications of synthetic, biopolymeric scaffolds as tunable treatment modalities for chronic wounds will be considered.